Promoting Organizational Performance in Cooperatives: The Role of Knowledge Sharing and Innovation Capability - Mardiana Andarwati; Yuntawati Fristin; Xie Qiong (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2024)
Cooperatives are the foundation of the Indonesian economy as it aligns with the nation’s principle to promote welfare. This present research is aimed at exploring the influence of knowledge sharing on innovation capabilities and comprehending the role of innovation capability as a mediator. This research elaborated on a sample of 139 managers of multi-enterprise cooperatives in Malang of Indonesia. The data were gathered through online questionnaires and employed Structural Equation Modeling (SEM) with the AMOS application as an analysis tool. The Research findings show that innovation capabilities are significantly influenced by knowledge sharing among leaders or managers in cooperatives. Accordingly, organizational performance is also explained by knowledge sharing. This study also confirms the role of innovation capabilities in mediating the connection between knowledge sharing and organizational performance in cooperatives. The output of this present research can be used by decision researchers and the government to enhance the performance of cooperatives, which in turn can drive welfare. Keywords: Innovation capability, Knowledge sharing, Organizational performance